Sex differences in sickness absence and the morbidity-mortality paradox: a longitudinal study using Swedish administrative registers - Bertil Lindahl; Daniel Avdic; Pathric Hägglund; Per Johansson (BMJ Open)
Objective To analyse whether gender-specific health behaviour can be an explanation for why women outlive men, while having worse morbidity outcomes, known as the morbidity-mortality or gender paradox.Setting The working population in Sweden.Participants Thirty per cent random sample of Swedish women and men aged 40–59 with a hospital admission in the 1993–2004 period were included. The sample for analysis consists of 233 274 individuals (115 430 men and 117 844 women) and in total 1 867 013 observations on sickness absence.Intervention Hospital admission across 18 disease categories.Main outcome measures The main outcome measures were sickness absence (morbidity) and mortality. Longitudinal data at the individual level allow us to study how sickness absence changed after a hospital admission in men and women using a difference-in-differences regression analysis. Cox regression models are used to study differences in mortality after the admission.Results Women increased their sickness absence after a hospital admission by around five more days per year than men (95% CI 5.25 to 6.22). At the same time, men had higher mortality in the 18 diagnosis categories analysed. The pattern of more sickness absence in women was the same across 17 different diagnosis categories. For neoplasm, with a 57% higher risk of death for men (54.18%–59.89%), the results depended on the imputation method of sickness for those deceased. By using the premortality means of sickness absence, men had an additional 14.47 (-16.30– -12.64) days of absence, but with zero imputation women had an additional 1.6 days of absence (0.05–3.20). Analyses with or without covariates revealed a coherent picture.Conclusions The pattern of increased sickness absence (morbidity) and lower mortality in women provides evidence on the more proactive and preventive behaviour of women than of men, which could thus explain the morbidity-mortality paradox.